Prevalencia de la disfunción temporomandibular en trabajadores de la industria. Asociación con el estrés y el trastorno del sueño - Martins, Ronald J.; Saliba-Garbin, Cléa Adas; Cândido, Nádia Biage; Ísper Garbin, Artênio J.; Saliba Rovida, Tânia A. (Universidad Nacional de Colombia, 2016)
Objective: To determine the presence of temporomandibular disorders (TMD), sleep disorders and stress, as well as the association between these factors, among industrial workers in São Paulo State, Brazil. Material and Methods: Fonseca’s questionnaire was used to verify the level of TMD, the Toronto Sleep Assessment Questionnaire (SAQ) was applied to check the quality and occurrence of sleep disorders, and the Social Readjustment Rating Scale (SRRS) was used to check the degree of stress. The data collected were tabulated with Epi Info™ 7 and statistically analyzed using the chi-square test, with a 5 % significance level. Results: 104 workers participated in the survey. Most were male (74 %) between 35 and 44 years of age (26 %). Thirty-seven (35.6 %) had some degree of disorder, 65 (62.5 %) presented with sleep disorders, and 6 (5.8 %) presented with higher degrees of stress. After statistical analysis, there was no significant association between stress and temporomandibular disorders (TMD). However, there was an association between quality ofsleep and sex ofthe individual with TMD (p<0.01). Conclusion: We conclude that a high percentage ofthe analyzed population has sleep disorders and TMD. Sex and the quality ofsleep influence the occurrence of TMD.
Prevalence of temporomandibular disorders among industrial workers. Association with stress and sleep disorder
Keywords: Burnout; Occupational health; Professional; Sleep disorders; Temporomandibular joint dysfunction syndrome